A climatic classification for geomorphological purposes - Beyer, Lutz (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1981)
In this paper we reconsider the definition of climatic geomorphological zones, which until now has been merely descriptive. By excluding the sub-glacial zone, azonal mountain regions and adibiatic deserts, it is possible to recognize six zones which are essentially different and characterized by specific types of morphogenesis. Each is categorized according to typical processes and landforms and delineated by means of meteorological threshold values: 1. The subpolar zone of solifluction and frost-shattered debris. 2. The moderate zone of modicofluvial action and relict forms. 3. The subtropical zone of slope wash and seasonal rivers. 4. The paratropical zone of eolian action and dry debris. 5. The tropical zone of sheet wash and inselbergs. 6. The innertropical zone of landsliding and valleys.